Aptamer for imaging and therapeutic targeting of brain tumor glioblastoma. (17th July 2015) - Delač, Mateja; Motaln, Helena; Ulrich, Henning; Lah, Tamara T.
Abstract Aptamers are short single‐stranded nucleic acids (RNA or ssDNA), identified by an in vitro selection process, denominated SELEX, from a partially random oligonucleotide library. They bind to a molecular target, a protein or other complex macromolecular structures of interest with high affinity and specificity, comparable to those of antibodies. Recently, aptamer selection protocols were developed for targeting living cells, including tumors. Chemical modifications of the aptamers and modalities of their detection and delivery systems are already available with high selectivity and targeting ability for the desired cancer cell type, making them promising for diagnosis and therapy. Glioblastoma multiformae represents the most malignant and fatal stage of glioma, and is also the most frequent brain tumor. Glioblastoma‐specific aptamers were developed by either targeting the whole cell surface or known glioma biomarkers. These aptamers may gain importance for imaging, tumor cell isolation from biopsies and drug delivery. In biomedical imaging techniques, aptamers coupled with radionuclide or fluorescent labels, bioconjugates and nanoparticles offer an advanced, noninvasive manner for defining the glioblastoma tissue border. Though single modality aptamer imaging probes have some limitations, these are overcome by the use of multimodal probes. Due to selectivity and chemical characteristics, aptamers can be coupled to functionalized nanoparticles and loaded with a drug, appeared promising for in vivo targeting of glioblastoma. Finally, aptamers are effective mediators for gene silencing when coupled to small interfering RNA and a viral vector, thus providing a novel tool with enhanced targeting capability in drug delivery, designed for tailored treatment of glioblastoma patients. © 2015 International Society for Advancement of Cytometry